2013
DOI: 10.1177/0954411912473398
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb relation during the double support phase of gait: An electromyographic, mechanical and energy-based analysis

Abstract: Purpose: To analyse the interlimb relation and the influence of mechanical energy on metabolic energy expenditure during gait. Methods: 22 subjects were monitored as to electromyographic activity (EMG), ground reaction forces (GRF) and VO 2 consumption (metabolic power) during gait. Results: A moderate negative correlation was observed between the activity of tibialis anterior (TA), biceps femoris (BF) and vastus medialis (VM) of the trailing limb (TRAIL) during mid-stance to double support transition (MS-DS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…In spite of occurring mainly during DS, biomechanical models suggest that energy loss during step-to-step transition can be reduced by a propulsion impulse from the TRAIL limb immediately before collision of the LEAD limb 5 . Also, studies about interlimb relation in healthy subjects demonstrate a relation between muscle activity of the TRAIL limb during terminal stance and biomechanical parameters of the LEAD limb during initial contact and loading response 9,10 . Thus, the stance phase was …”
Section: Data Processing A) Kinetic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of occurring mainly during DS, biomechanical models suggest that energy loss during step-to-step transition can be reduced by a propulsion impulse from the TRAIL limb immediately before collision of the LEAD limb 5 . Also, studies about interlimb relation in healthy subjects demonstrate a relation between muscle activity of the TRAIL limb during terminal stance and biomechanical parameters of the LEAD limb during initial contact and loading response 9,10 . Thus, the stance phase was …”
Section: Data Processing A) Kinetic Parametersmentioning
confidence: 99%
“…An optimal mechanical relation between human limbs has been described as the trailing limb (TRAIL) plantar flexor action 6,7 compensates the energy loss provoked by the leading limb (LEAD) during heel strike 5,8 to maintain the velocity of the body's centre of mass. Recent studies involving healthy subjects have demonstrated that the degree of plantar flexor activity during propulsion depends on the degree of muscle activity 9 and on the magnitude of the ground reaction force 10 of the contralateral limb during heel strike. This interlimb relation observed during step-to-step transition of unimpaired walking 9,10 , and also in standing-related tasks 11,12 , can be justified by the bilateral influence of group II fibres on spinal interneurons 13 and by the importance of vestibulo-and reticulo-spinal pathways on group II fibres 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study of these tasks must focus the subphases with higher postural control demand, i.e. the initial phase of sit-to-stand and standto-sit (Silva et al, 2012b;Silva et al, 2012c), middle stance (Silva et al, 2012d;, double support (Silva et al, 2015;Sousa et al, 2013a;Sousa et al, 2013b) and gait initiation (Sousa et al, 2015a(Sousa et al, , 2015b.…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%
“…The sit-to-stand-to-sit and walking are good examples of this type of task (de Souza et al, 2011;Dehail et al, 2007;Galli et al, 2008;Hase et al, 2004) since they involve the coordination of joints along the kinematic chain to keep the centre of mass within the safe limits of the body's base of support (Freitas et al, 2009;Jacobs, 1997;Kiemel et al, 2008;Morasso et al, 1999;Nicholas et al, 1998;van der Kooij et al, 1999). Additionally, the lower limbs must be coordinated to provide support and stability (Sousa et al, 2013b), being recognised by the central nervous system as one functional unit. The study of tasks involving this functional unit enables identifying any atypical behaviour, since it depends on the role of the reticulospinal system in interlimb regulation (Schepens et al, 2004).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%